Madheshi Women’s Struggle for Higher Education in Nepal - Khanal, Hota Raj (Education and Development, 2021)
This article adopted a qualitative approach to explore the practices and problems faced by Madheshi women in higher education. Though the traditional world has changed, and women in Madhesh are still struggling for equality and empowerment. For achieving higher education, they are accepting all the challenges that rise in front of them; but the established traditional norms and values in their socio-cultural life have become the main barriers playing role in keeping them away from higher education. In this study, the primary data were collected via in-depth interview with the participant with prolonged engagement in the field. The interpretation and analysis of the data helped to reach the conclusion from the perspective of the participant. The finding revealed that tit-bits of Madheshi women are receiving higher education but lots of them are away from education; engaged in household works, rearing children, feeding the family members; and socio-cultural beliefs have suppressed them a lot.